Association between eating behavior and smoking, use of illicit drugs and depressive episodes in adolescents - Piazzon GOMES, Juliany (2010)
ObjectiveThe goal of this study was to identify the prevalence of symptoms of eating disorders in female students enrolled in state elementary schools and investigate a possible association between these eating disorders andsmoking, illicit drug use and depressive episodes. MethodsThe Bulimic Investigatory Test of Edinburgh with symptom and severity scales and the Eating Attitudes Test - 26 with additional questions on smoking, illicit drug use and depressive episodes were used. The sample consisted of roughly 300 female students aged 10 to 15 years. ResultsThe results showed that 4.2% and 3.6% of the students presented symptoms of eating disorders according to the Bulimic Investigatory Test of Edinburgh and Eating Attitudes Test - 26, respectively. The rates of smoking, illicit drug use and depressive episodes were 4.2%, 4.9% and 10.7%, respectively. Depressive episodes were significantly associated with the following parameters: Bulimic Investigatory Test of Edinburgh - symptom scale (p=0.04) and Bulimic Investigatory Test of Edinburgh - severity scale (p=0.02). Smoking (p=0.01) and illicit drug use (p=0.04) were also associated with the Bulimic Investigatory Test of Edinburgh - symptom scale. ConclusionThis study found that these students were at high risk of developing risky behaviors, such as eating disorders and depressive episodes.